WY-14643, a Potent Peroxisome Proliferator Activator Receptor-α PPAR-α Agonist Ameliorates the Inflammatory Process Associated to Experimental Periodontitis - Enrico Briguglio; Rosanna Di Paola; Irene Paterniti; Emanuela Mazzon; Giacomo Oteri; Giancarlo Cordasco; Salvatore Cuzzocrea (PPAR Research)
We have investigated the effects of WY14643, a potent peroxisome proliferator activator receptor-α (PPAR-α) agonist, in a rat model of ligature-induced periodontitis. Male Sprague-Dawley rats were lightly anaesthetized with pentobarbitone (35 mg/kg). Sterile, 2-0 black braided silk thread was placed around the cervix of the lower left first molar and knotted medially. Animals received WY14643 (1 mg/kg i.p, daily for eight days). Eighths days after placement of the ligature, we evaluated several markers of inflammation such us (1) myeloperoxidase activity, (2) a cytokines and adhesion molecules expression, (3) NF-κB expression, (4) iNOS expression, (5) the nitration of tyrosine residues, (6) activation of the nuclear enzyme poly(ADP-ribose) polymerase, (7) apoptosis, and (8) the degree of gingivomucosal tissues injury. Administration of WY14643 significantly decreased all of the parameters of inflammation as described above. These results demonstrate that WY14643 exerts an anti-inflammatory role during experimental periodontitis and is able to ameliorate the tissue damage.